Planning and control using Oracle Primavera P6 - versions 8.2 & 8.3 EPPM web : "Enterprise Portfolio Project Management" - Harris, Paul Eastwood (Eastwood Harris Pty Ltd., 2014)
This user guide is a reference book and two-day training course written for project management professionals who wish to learn how to plan and control both an unresourced and resourced project in an Oracle Primavera "Enterprise Project Portfolio Management" environment. This updated edition includes the new features of Oracle Primavera P6 Versions 8.3 Web. It is packed with screen shots, constructive tips and contains workshops with solutions at the end of each chapter for the reader to practice the skills taught. It has been written for use with the EPPM Web tool and is geared toward people who wish to learn the software but are unable to attend a training course and find the software reference manual hard going; project management companies who wish to run their own software training courses or provide their employees with an alternative text to the vendor supplied user manual; training organizations requiring a training manual to run their own training courses. --